Peer-to-Peer Sharing of Social Media Messages on Sexual Health in a School-Based Intervention: Opportunities and Challenges Identified in the STASH Feasibility Trial - Hirvonen, Maija; Purcell, Carrie; Elliott, Lawrie; Bailey, Julia V; Simpson, Sharon Anne; McDaid, Lisa; Moore, Laurence; Mitchell, Kirstin Rebecca (JMIR Publications, 2021)
BackgroundThere is a strong interest in the use of social media to spread positive sexual health messages through social networks of young people. However, research suggests that this potential may be limited by a reluctance to be visibly associated with sexual health content on the web or social media and by the lack of trust in the veracity of peer sources. ObjectiveThe aim of this study was to investigate opportunities and challenges of using social media to facilitate peer-to-peer sharing of sexual health messages within the context of STASH (Sexually Transmitted Infections and Sexual Health), a secondary school-based and peer-led sexual health intervention. MethodsFollowing training, and as a part of their role, student-nominated peer supporters (aged 14-16 years) invited school friends to trainer-monitored, private Facebook groups. Peer supporters posted curated educational sex and relationship content within these groups. Data came from a feasibility study of the STASH intervention in 6 UK schools. To understand student experiences of the social media component, we used data from 11 semistructured paired and group interviews with peer supporters and their friends (collectively termed students; n=42, aged 14-16 years), a web-based postintervention questionnaire administered to peer supporters (n=88), and baseline and follow-up questionnaires administered to students in the intervention year group (n=680 and n=603, respectively). We carried out a thematic analysis of qualitative data and a descriptive analysis of quantitative data. ResultsMessage sharing by peer supporters was hindered by variable engagement with Facebook. The trainer-monitored and private Facebook groups were acceptable to student members (peer supporters and their friends) and reassuring to peer supporters but led to engagement that ran parallel to-rather than embedded in-their routine social media use. The offline context of a school-based intervention helped legitimate and augment Facebook posts; however, even where friends were receptive to STASH messages, they did not necessarily engage visibly on social media. Preferences for content design varied; however, humor, color, and text brevity were important. Preferences for social media versus offline message sharing varied. ConclusionsInvitation-only social media groups formed around peer supporters' existing friendship networks hold potential for diffusing messages in peer-based sexual health interventions. Ideally, interactive opportunities should not be limited to single social media platforms and should run alongside offline conversations. There are tensions between offering young people autonomy to engage flexibly and authentically and the need for adult oversight of activities for information accuracy and safeguarding.